Tipologi Hubungan Majaz ‘Aqli dalam Hadis Akhir Zaman: Konstruksi Linguistik dan Implikasi Teologisnya - Aang Saeful Milah; Siti Ba’i Muhibah; Suciati Fatimah; Siti Padlah; Muhammad Faiq Dhiyaulhaq (LPPM IAIN Sorong, 2026)
Contemporary studies of Islamic eschatological texts are often influenced by literal interpretations that may overlook their rhetorical dimensions and lead to theological misunderstandings in the digital era. This study aims to identify, classify, and analyze the types of Majaz 'Aqli (logical metaphor) found in end-time hadiths and to examine their theological implications. The research employs a qualitative library research method using a textual-hermeneutic approach based on classical Arabic rhetoric (Balaghah). Data were purposively selected from the canonical collections of al-Kutub al-Sittah, resulting in four representative hadiths that illustrate different forms of 'alaqah (semantic relations). The findings reveal four major categories of Majaz 'Aqli: sababiyyah (causal relation) in narrations concerning Dajjal, zamaniyyah (temporal relation) in descriptions of the shortening of time, makaniyyah (spatial relation) in depictions of the earth’s destruction, and mashdariyyah (source relation) in narrations about the blowing of the trumpet. Classical commentaries confirm that these expressions are not intended literally but rhetorically. The study concludes that understanding these rhetorical devices helps prevent theological errors, such as fatalism, anthropomorphism, and excessive materialism, while promoting a more balanced and contextual interpretation of hadith